Diabetes insipidus: The other diabetes - Kalra, Sanjay (Indian J Endocrinol Metab, 2016)
Diabetes insipidus (DI) is a hereditary or acquired condition which disrupts normal life of persons with the condition; disruption is due to increased thirst and passing of large volumes of urine, even at night. A systematic search of literature for DI was carried out using the PubMed database for the purpose of this review. Central DI due to impaired secretion of arginine vasopressin (AVP) could result from traumatic brain injury, surgery, or tumors whereas nephrogenic DI due to failure of the kidney to respond to AVP is usually inherited. The earliest treatment was posterior pituitary extracts containing vasopressin and oxytocin. The synthetic analog of vasopressin, desmopressin has several benefits over vasopressin. Desmopressin was initially available as intranasal preparation, but now the oral tablet and melt formulations have gained significance, with benefits such as ease of administration and stability at room temperature. Other molecules used for treatment include chlorpropamide, carbamazepine, thiazide diuretics, indapamide, clofibrate, indomethacin, and amiloride. However, desmopressin remains the most widely used drug for the treatment of DI. This review covers the physiology of water balance, causes of DI and various treatment modalities available, with a special focus on desmopressin.